2006
DOI: 10.1080/10428190500254208
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus-associated post-transplant lymphoproliferative disease with central nervous system involvement after unrelated allogeneic hematopoietic stem cell transplantation

Abstract: Post-transplant lymphoproliferative disorders (PTLD) represent an heterogeneous group of abnormal lymphoid proliferation related to Epstein-Barr virus (EBV) reactivation that arise early after allogeneic hematopoietic stem cell transplant (HSCT). PLTD with central nervous system (CNS) involvement has been reported in few cases. We describe the case of a 31-year-old-man who developed an EBV-related PTLD with CNS involvement 2 months after an allogeneic unrelated HSCT for acute myeloid leukemia in first complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 13 publications
(12 reference statements)
0
31
0
Order By: Relevance
“…The following first-line treatment of PTLD is recommended: (i) anti-CD20 therapy (rituximab) (AII); 151,[171][172][173] (ii) reduction of immunosuppressive therapy, if possible (BII); (iii) adoptive immunotherapy with in vitro-generated donor EBVcytotoxic T-cells, if available (CII); 168,174 and (iv) infusion of donor lymphocytes (DLI) to restore T-cell reactivity (CIII). Generally recommended both for preemptive and symptomatic therapy is the use of anti-CD20 MoAbs, in spite of lack of randomized trials.…”
Section: Treatment Of Ptldmentioning
confidence: 99%
“…The following first-line treatment of PTLD is recommended: (i) anti-CD20 therapy (rituximab) (AII); 151,[171][172][173] (ii) reduction of immunosuppressive therapy, if possible (BII); (iii) adoptive immunotherapy with in vitro-generated donor EBVcytotoxic T-cells, if available (CII); 168,174 and (iv) infusion of donor lymphocytes (DLI) to restore T-cell reactivity (CIII). Generally recommended both for preemptive and symptomatic therapy is the use of anti-CD20 MoAbs, in spite of lack of randomized trials.…”
Section: Treatment Of Ptldmentioning
confidence: 99%
“…Because monotherapy with rituximab is reported to rescue 63% patients with PTLD 14 , we expected that rituximab therapy would not be able to cure a fulminant EBV-PTLD as seen in our case even in combination with DLI. Cidofovir, a monophosphate nucleotide analogue of cytosine that inhibits viral DNA polymerase, is effective in treating various kinds of viral infections due to adenovirus 15 , BK virus 16 , and EBV [17][18][19] . Although the addition of cidofovir to rituximab-DLI therapy may have helped the patient to overcome such a disastrous condition without obvious adverse effects, there is little evidence to suggest therapeutic efficacy against EBV 14,20 .…”
Section: Discussionmentioning
confidence: 99%
“…Rituximab has shown promising activity in systemic PTLD, but Pakakasama et al 6 reported no response of primary CNS PTLD to rituximab therapy, suggesting that CNS penetration might be poor. In contrast, Nozzoli et al 4 reported complete response of CNS PTLD with intravenous rituximab, cidofovir and intrathecal methotrexate and methylprednisolone in a patient with leptomeningeal disease without focal brain lesions. It is not clear whether the same response could be obtained with rituximab alone.…”
mentioning
confidence: 96%
“…Donor lymphocyte infusion carries the risk of causing GVHD and has not been shown to be effective in CNS PTLD. 4 Pakakasama et al 6 reported favorable response of CNS PTLD to a combination of EBV-specific cytotoxic T cells (EBV-CTL) with hydroxyurea. EBV-CTLs are, however, not widely available and can take months to generate.…”
mentioning
confidence: 99%
See 1 more Smart Citation